Seismic Performance Evaluation and Design of Multi-Storey Buildings - Vijay Kumar Pandit; Akshit Lamba; Indra Narayan Yadav (International Journal of Scientific Research in Civil Engineering, 2025)
The primary objective of this study is to design and comparatively analyze a G+6 residential structure using ETABS and STAAD.Pro. Traditional manual design approaches are highly time-consuming and involve complex calculations, whereas modern software provides faster and more accurate results. These tools are user-friendly, efficient for research and design, and ensure greater precision in structural analysis. In this work, the design is carried out by applying the Limit State Method in accordance with relevant Indian Standard Codes and Practices. Both ETABS and STAAD.Pro are capable of advanced analysis, including finite element modeling, dynamic analysis, and result verification. STAAD.Pro, in particular, offers an intuitive interface, powerful design engines, visualization tools, and reliable assessment capabilities, making it one of the most preferred software among engineers. For the analysis, the G+6 structure is subjected to Dead Load, Live Load, Wind Load, and Seismic Load, with their combinations considered as per IS codes. The modeling process involves defining cross-sections of beams and columns, slab thickness, material properties, and boundary conditions. Once loads are applied, the model is analyzed through “Run Analysis” to check whether the structure is safe under the applied load combinations. Finally, a comparative study is conducted between ETABS and STAAD.Pro, focusing on the design of beams and columns. The outcome highlights which software provides a more effective and time-efficient solution for the design and analysis of multi-storey buildings.
Keywords: ETABS and STAAD; G+6 structure; Seismic